Long-Term Immuno-Response and Risk of Breakthrough Infection After SARS-CoV-2 Vaccination in Kidney Transplantation - Vincenzo Bellizzi; Mario Fordellone; Carmine Secondulfo; Paolo Chiodini; Giancarlo Bilancio (Vaccines)
Background: Kidney transplant (KTx) recipients exhibit impaired responses to SARS-CoV-2 vaccination. Correlates of vaccine-induced immunity and risk factors for breakthrough infection are not fully defined. This study evaluated the humoral response trajectories and determinants of breakthrough infection in KTx recipients. Methods: KTx recipients received two doses of the BNT162b2 mRNA vaccine three weeks apart and a booster after six months. Patients were categorized based on pre-vaccination status: previous COVID-19 disease (DIS), asymptomatic SARS-CoV-2 infection (INF), or infection-naïve (NEG). Serum anti-spike antibody titers were assessed at baseline, before the second dose, and at 1, 3, 6, 9, and 12 months. Linear mixed models and survival analyses were performed. Results: Of 326 enrolled patients, 189 with complete time-point data were included in the longitudinal analysis. Antibodies were detectable in 89% of DIS/INF at baseline and 91% before the second dose, but were negligible in NEG. In NEG, the seropositivity increased after vaccination and booster, reaching 78% at 12 months. Age (−5% per year, p < 0.001) and BMI (+10% per unit, p = 0.004) influenced titers; antimetabolites and steroids had strong negative effects (−70%, p = 0.005; −84%, p = 0.001). Breakthrough infections occurred in 104 (31.9%); 40% were asymptomatic, and 2 patients died. An mTOR inhibitor was associated with a reduced infection risk (OR 0.27 [CI: 0.09–0.70], p = 0.009). Higher antibody titers correlated with delayed infection (p = 0.063). Conclusions: In KTx patients, humoral response to SARS-CoV-2 vaccination is limited in infection-naïve patients but improved by booster dosing; the hybrid immunity is more effective. Immunosuppressive regimens influence the immune response, and mTOR inhibitors may protect against breakthrough infection.